“Russell Banks goes Creole”: A Talk with the Author of The Book of Jamaica and Continental Drift - Kathleen Gyssels (Association Française d'Etudes Américaines, 2008)
This interview with Russell Banks, acknowledged author of The Book of Jamaica (1980) and Continental Drift (1985), amongst others, was conducted on May 27th 2007 by Kathleen Gyssels and Gaëlle Cooreman (University of Antwerp). The main topics included are Banks’ idea of the Great American Novel, his involvement with the African diaspora and his « Caribbean » novels The Book of Jamaica and Continental Drift.